Development of Story Electronic Module With Pancasila Student Profiles For Improving Cultural Literature - Andi Maulana; Subyantoro Subyantoro; Tommi Yuniawan; Rahayu Pristiwati (Universitas Negeri Semarang, 2022)
There needs to be a module that can help students learn Indonesian independently and also tools that are in accordance with the needs of UNBK, so that learning objectives can be achieved. Development of an electronic saga module containing the profile of Pancasila students to increase cultural literacy in SMA. The purpose of this study is to develop, compile, test the feasibility and effectiveness of an electronic module containing a profile of Pancasila students in Indonesian class X SMA in Semarang City. The ADDIE model is an iterative instructional design process, where the results of the formative evaluation of each stage can lead to a return to each of the previous stages. The final product from one phase of the results of formative evaluation is the initial product to start to the stages in between, 1) the initial product design stage (Design), 2) the product development stage (Development), 3) the product implementation stage (Implementation), 4) test validation by experts and Indonesian language teachers, 5) product evaluation stage (Evaluation). The results of the analysis of the needs of educators and students through the various methods mentioned above, the researcher provides a common thread that is important to develop an electronic saga module that imposes a Pancasila student profile on high school students in Semarang City. The product being developed is a continuation of the E-Module that is used in SMA Kota Semarang, especially the printed E-Module. But by paying attention and considering all aspects needed by students so that the learning process using this E-Module is in accordance with the character and conditions and the shared needs of both educators and students. The main characteristic of the developed E-Module lies in the media used, namely audio-visual, with the media students will be stimulated to practice their skills,